EROSIVE OSTEOARTHRITIS: A RARE CASE REPORT (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Osteoarthritis, also known as OA, is a type of joint degeneration characterized by changes in the morphology and biochemistry of the synovial membrane and joint capsule, as well as degradation of cartilage joint and expansion of the marginal bone. Inflammation causes the joints to deteriorate in a subtype of osteoarthritis called erosive OA. DIP (distal interphalangeal), PIP (proximal interphalangeal), CMC (carpometacarpal) and metacarpophalangeal (MCP) joints are the most often affected joints in the hand. Other joints in other body regions are extremely seldom affected. Our patient’s diagnosis report suggests erosive osteoarthritis and seronegative arthritis as negative anti-RF factors.